Electrophotographic Device
Patent Information
- Application Number
- JP2021106837
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-06-28
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2041-06-28
AI Technical Summary
Existing electrophotographic devices face issues with photoreceptor wear and shortened lifespan due to the use of strontium titanate fine particles, which adversely affect image formation and environmental stability.
Incorporating an outermost layer containing a silica filler with externally added silica and strontium titanate fine powder treated with a silane compound to enhance the photoreceptor's abrasion resistance and chargeability, using a toner with a specific composition to improve the photoreceptor's longevity.
The solution results in a long-life electrophotographic photoreceptor with maintained environmental stability by reducing wear and optimizing chargeability, enhancing the photoreceptor's durability and image quality.
Smart Images

Figure 00000019_0000 
Figure 00000019_0001
Abstract
Description
Technical Field
[0001] The present invention relates to an electrophotographic apparatus capable of realizing a long life of an electrophotographic photoreceptor (also referred to as a "photoreceptor") while maintaining environmental stability.
Background Art
[0002] In recent years, with the remarkable development of OA equipment, electrophotographic apparatuses (image forming apparatuses) such as copiers, printers, and facsimile machines using the electrophotographic method have been widely spread. Then, with the increase in the contact charging method by roller charging and the progress of the long life, miniaturization, and high speed of electrophotographic apparatuses such as digital copiers and printers, various functions are required for electrophotographic apparatuses and toners used therein.
[0003] For example, as a technique for improving environmental variations in image formation, Japanese Patent Application Laid-Open No. 2015-084095 (Patent Document 1) discloses a toner containing toner particles containing a binder resin, a wax, and a colorant, and silica fine particles and strontium titanate fine particles present on the surface of the toner particles. The silica fine particles have a specific number average particle size and are negatively charged, and are fixed to the surface of the toner particles at a specific coating rate and coating ratio. The strontium titanate fine particles are positively charged. Further, Patent Document 1 describes that strontium titanate fine particles whose surface is treated with a fatty acid or a fatty acid metal salt are preferable.
Prior Art Documents
Patent Documents
[0004]
Patent Document 1
Summary of the Invention
Problems to be Solved by the Invention
[0005] Patent Document 1 describes how environmental fluctuations in image formation are improved by including strontium titanate nanoparticles together with silica nanoparticles on the surface of toner particles. However, the technology described in Patent Document 1 has a problem in that, regardless of whether or not the surface treatment is performed, the physical properties of the strontium titanate nanoparticles themselves cause increased wear on the photoreceptor drum, adversely affecting image formation and shortening the life of the electrophotographic photoreceptor.
[0006] Therefore, the present invention aims to provide an electrophotographic apparatus that can achieve a longer lifespan for the electrophotographic photoreceptor while maintaining environmental stability. [Means for solving the problem]
[0007] The inventors of the present invention conducted diligent research to solve the above problems and, as a result, discovered that by using a toner to which externally added silica and a core surface of strontium titanate with added silica has been hydrophobized with a silane compound, in an electrophotographic apparatus equipped with a top surface layer containing silica filler, wear of the photoreceptor drum can be suppressed (polishing properties are improved) and a longer lifespan can be achieved, thus completing the present invention.
[0008] Thus, according to the present invention, in an electrophotographic apparatus that forms an electrostatic latent image on the surface of an electrophotographic photoreceptor and transfers developed toner onto a transfer material to form an image, The electrophotographic photoreceptor comprises a top surface layer containing silica filler, The toner comprises toner matrix particles containing at least a binder resin, a colorant, and a release agent, and an external additive as constituent components. An electrophotographic apparatus is provided, characterized in that the external additive is an external fine powder obtained by hydrophobizing the surface of a core containing external silica and strontium titanate with a silane compound. [Effects of the Invention]
[0009] According to the present invention, it is possible to provide an electrophotographic apparatus that can achieve a longer lifespan for the electrophotographic photoreceptor while maintaining environmental stability. In other words, according to the present invention, the edges of the strontium titanate in the externally added fine powder, which is hydrophobized with a silane compound on the silica-added core surface, become smooth (spheroidized), which moderately reduces abrasion on the photoreceptor drum, resulting in a longer lifespan and optimized electrostatic properties. [Brief explanation of the drawing]
[0010] [Figure 1] This is a schematic side view showing the configuration of the main parts of the electrophotographic apparatus of the present invention. [Figure 2] This is a schematic cross-sectional view showing the configuration of a key part of an example of an electrophotographic photoreceptor (stacked photoreceptor) included in the electrophotographic apparatus of the present invention. [Modes for carrying out the invention]
[0011] (1) Electrophotographic device The present invention relates to an electrophotographic apparatus that forms an electrostatic latent image on the surface of an electrophotographic photoreceptor and transfers developed toner onto a transfer material to form an image. The electrophotographic photoreceptor comprises a top surface layer containing silica filler, The toner comprises toner matrix particles containing at least a binder resin, a colorant, and a release agent, and an external additive as constituent components. The external additive is characterized in that it is an external fine powder obtained by hydrophobizing the surface of a core containing external silica and strontium titanate with a silane compound. The following describes the external additives that make up the characteristic components of the toner of the present invention, the toner matrix particles which are the basic components of the toner, the method for manufacturing the toner, the two-component developer containing the toner, and the electrophotographic apparatus to which the toner of the present invention is applied.
[0012] (1-1) External additives External additives generally have functions that improve toner transportability and electrostatic properties, as well as agitation with the carrier when the toner is used in a two-component developer. The toner additive of the present invention is an external fine powder obtained by hydrophobizing the surface of a core containing external silica and strontium titanate with a silane compound.
[0013] (1-1-1) External silica The added silica preferably has an average primary particle diameter of 40 nm or less. If the average primary particle size of the externally added silica exceeds 40 nm, the effect of imparting fluidity to the toner decreases, which can lead to toner scattering due to poor mixing. On the other hand, if the average primary particle size of the externally added silica is too small, embedding into the toner particles becomes significant, and the adjustment of charge and fluidity may not be sufficiently performed throughout extended use. The lower limit for this is around 6 nm. The preferred average primary particle size of the externally added silica is 6 to 17 nm, and more preferably 7 to 12 nm.
[0014] Examples of externally added silica include silica particles commonly used in the relevant art, such as fumed silica obtained by burning silicon tetrachloride, dry silica particles such as arc silica produced by micronizing silica in the gas phase using high energy such as plasma; wet silica particles such as precipitated silica synthesized under alkaline conditions using an aqueous sodium silicate solution as a raw material, and gel silica synthesized under acidic conditions; colloidal silica particles obtained by polymerizing acidic silicic acid in an alkaline state; and sol-gel silica particles obtained by hydrolysis of organosilane compounds. These may also be surface-treated with a surface treatment agent to improve the electrical properties of the photoreceptor. Examples of surface treatment agents include surface treatments commonly used in the art, such as hexamethyldisilazane (HMDS), dimethyl-dichlorosilane (DDS), octylsilane (OTAS), and polydimethylsiloxane (PDMS). Commercially available hydrophobized silica particles may be used, or unhydrophobized silica particles may be subjected to treatment before use.
[0015] (1-1-2) Externally added fine powder The externally added fine powder has a hydrophobic surface treatment with a silane compound on the core surface obtained by adding silica to strontium titanate. The externally added fine powder is not particularly limited, but can be produced, for example, by the following method. A solution 1 obtained by adjusting the pH of metatitanic acid to 1.0 with hydrochloric acid and peptizing it, a solution 2 of an aqueous strontium chloride solution, and a solution 3 of an aqueous sodium silicate solution are mixed at a ratio such that the molar ratio of (Sr + Si) / Ti becomes 1.2. The resulting mixed solution is heated to 80°C under a nitrogen gas atmosphere, and an aqueous sodium hydroxide solution is added thereto at a rate of 1 equivalent / hour, and the obtained fine powder is surface-coated with a silane coupling agent by a surface treatment method commonly used in the art. Examples of the silane coupling agent include hexamethyldisilazane (HMDS), dimethyl-dichlorosilane (DDS), octylsilane (OTAS), and polydimethylsiloxane (PDMS).
[0016] The molar ratio Si / Ti of silicon Si of silica and titanium Ti of strontium titanate in the externally added fine powder is not particularly limited, but is preferably 0.03 or more and less than 1.0. When the molar ratio Si / Ti is less than 0.04, the conductivity of the externally added fine powder increases, and when the toner added with it is left in a high-humidity environment, the charge decay rate becomes fast and the fog value may increase. On the other hand, when the molar ratio Si / Ti is 1 or more, due to the strong negative charging characteristics of silica, when the toner added with the externally added fine powder is continuously printed in a low-humidity environment, the charging of the toner becomes excessive, and the mixing with the toner replenished from the cartridge deteriorates, and the fog value due to toner scattering may increase.
[0017] The average primary particle size of the externally added fine powder is about 30 to 50 nm. The average primary particle size of the externally added fine powder is preferably larger than the average primary particle size of the externally added silica. Also, when the average primary particle size of the externally added fine powder is smaller than the average primary particle size of the externally added silica, the abrasiveness may not be exhibited. The preferable average primary particle size of the externally added fine powder is 35 to 45 nm.
[0018] (1-1-3) Dosage of externally added externally added agent The amount of externally added silica corresponds to a coverage rate of 50-120% of the toner matrix particles. If the amount of externally added silica corresponds to a coverage rate of less than 50% of the toner matrix particles, the charge of the toner will decrease, but its fluidity may also decrease. On the other hand, if the amount of externally added silica corresponds to a coverage rate of more than 120% of the toner matrix particles, the externally added silica may detach from the toner matrix particles and contaminate the developer. The preferred amount of externally added silica is an amount corresponding to a coverage rate of 50-150% of the toner matrix particles, and more preferably 80-100%.
[0019] The amount of externally added fine powder is preferably equivalent to a coating rate of 2 to 10% of the toner base particles. If the amount of externally added fine powder corresponds to a coverage rate of less than 2% of the toner base particles, the effects of the present invention may not be realized. On the other hand, if the amount of externally added fine powder corresponds to a coverage rate of more than 10% of the toner base particles, the effect of the fine powder in suppressing the charge of the toner becomes too large, and the charge may decrease too much. A more preferable amount of externally added fine particles is an amount corresponding to a coverage rate of 3-6% of the toner base particles.
[0020] Here, "coverage rate" is defined as the value calculated from the average primary particle diameter of the external additive and the surface area of the toner matrix particles, assuming that each particle of the external additive has the same average primary particle diameter, with 100% representing the state when the entire surface of the toner matrix particles is covered with the external additive in a close-packed state. The specific method for measuring the amount of external additive is described in the examples.
[0021] (1-1-4) Adhesion strength of external additives In the toner of the present invention, it is preferable that the ratio b / a, which is the adhesion strength b of the externally added fine powder to the toner mother particles and the adhesion strength a of the externally added silica, satisfies the relationship 0.15 ≤ α ≤ 0.5. If the adhesion strength ratio b / a is less than 0.25, the adhesion strength b of the externally added fine powder is weak, causing the externally added fine powder to detach from the toner matrix particles, and the desired electrostatic properties may not be achieved. On the other hand, if the adhesion strength ratio b / a exceeds 0.5, the adhesion strength b of the externally added fine powder is strong, causing the externally added fine powder to not detach from the toner matrix particles, and the cleaning effect may not be obtained. Here, the cleaning effect is achieved when the externally added fine powder is appropriately separated from the toner matrix particles and exists between the photoreceptor drum and the cleaning roller. A more preferable adhesion strength ratio b / a is 0.20 ≤ α ≤ 0.3. The specific method for measuring adhesion strength is described in the examples.
[0022] (1-2) Toner matrix particles The toner matrix particles contained in the toner of the present invention include at least a binder resin, a colorant, and a release agent, and may optionally contain known additives, to the extent that they do not impair the effects of the present invention.
[0023] (1-2-1) Binding resin A polyester-based resin can be suitably used as the binder resin included in the toner of the present invention. Polyester resins are typically obtained by performing a condensation polymerization, esterification, or transesterification reaction on one or more components selected from divalent alcohol components and trivalent or higher polyvalent alcohol components, and one or more components selected from divalent carboxylic acids and trivalent or higher polyvalent carboxylic acids, using known methods. The conditions for the condensation polymerization reaction can be appropriately set depending on the reactivity of the monomer components, and the reaction should be terminated when the polymer achieves desirable physical properties. For example, the reaction temperature is around 170-250°C, and the reaction pressure is around 5 mmHg to atmospheric pressure.
[0024] Examples of divalent alcohol components include alkylene oxide adducts of bisphenol A such as polyoxypropylene(2.2)-2,2-bis(4-hydroxyphenyl)propane, polyoxypropylene(3.3)-2,2-bis(4-hydroxyphenyl)propane, polyoxypropylene(2.0)-2,2-bis(4-hydroxyphenyl)propane, polyoxypropylene(2.0)-polyoxyethylene(2.0)-2,2-bis(4-hydroxyphenyl)propane, and polyoxypropylene(6)-2,2-bis(4-hydroxyphenyl)propane; ethyleneglyceride Examples include diols such as cellulose, diethylene glycol, triethylene glycol, 1,2-propylene glycol, 1,3-propylene glycol, 1,4-butanediol, neopentyl glycol, 1,4-butenediol, 1,5-pentanediol, 1,6-hexanediol, 1,4-cyclohexanedimethanol, dipropylene glycol, polyethylene glycol, polypropylene glycol, and polytetramethylene glycol; bisphenol A; propylene adducts of bisphenol A; ethylene adducts of bisphenol A; and hydrogenated bisphenol A.
[0025] Examples of polyhydric alcohol components with a valency of 3 or higher include sorbitol, 1,2,3,6-hexanetetrol, 1,4-sorbitan, pentaerythritol, dipentaerythritol, tripentaerythritol, sucrose, 1,2,4-butanetriol, 1,2,5-pentanetriol, glycerol, 2-methylpropanetriol, 2-methyl-1,2,4-butanetriol, trimethylolethane, trimethylolpropane, and 1,3,5-trihydroxymethylbenzene. In the toner of the present invention, one of the above-mentioned divalent alcohol components and trivalent or higher polyvalent alcohol components can be used alone or in combination of two or more.
[0026] Examples of divalent carboxylic acids include maleic acid, fumaric acid, citraconic acid, itaconic acid, glutaconic acid, phthalic acid, isophthalic acid, terephthalic acid, cyclohexanedicarboxylic acid, succinic acid, adipic acid, sebatic acid, azelaic acid, malonic acid, n-dodecenylsuccinic acid, n-dodecylsuccinic acid, n-octylsuccinic acid, isooctenylsuccinic acid, isooctylsuccinic acid, and their acid anhydrides or lower alkyl esters.
[0027] Examples of polycarboxylic acids with three or more valent values include 1,2,4-benzenetricarboxylic acid, 1,2,5-benzenetricarboxylic acid, 2,5,7-naphthalentricarboxylic acid, 1,2,4-naphthalentricarboxylic acid, 1,2,4-butanetricarboxylic acid, 1,2,5-hexanetricarboxylic acid, 1,3-dicarboxyl-2-methyl-2-methylenecarboxypropane, 1,2,4-cyclohexanetricarboxylic acid, tetra(methylenecarboxyl)methane, 1,2,7,8-octanetetracarboxylic acid, pyromellitic acid, empoletrimeric acid, and their acid anhydrides or lower alkyl esters. In the toner of the present invention, one of the above-mentioned divalent carboxylic acids and trivalent or higher polyvalent carboxylic acids can be used alone or in combination of two or more.
[0028] In the toner of the present invention, the binder resin preferably has a mass-average molecular weight in the range of 9,000 to 90,000, and the proportion of molecules with a molecular weight of 100,000 or more in its molecular weight distribution is preferably 10 to 30%. If the mass-average molecular weight and the proportion of molecules with a molecular weight of 100,000 or more of the binder resin are within the above range, the effect of achieving both low-temperature fixing performance and hot offset resistance in the belt fixing device will be further enhanced. If the mass-average molecular weight of the binder resin is less than 9,000, the release properties at high temperatures during fixation may be poor. On the other hand, if the mass-average molecular weight of the binder resin exceeds 90,000, the low-temperature fixation properties may be poor. By setting the mass-average molecular weight of the binder resin to 20,000 or more, the release properties at high fixing temperatures can be made even more reliable, while by setting the mass-average molecular weight of the binder resin to 70,000 or less, the low-temperature fixing properties can be made even more reliable. Therefore, a more preferable range for the mass-average molecular weight of the binder resin is 20,000 to 70,000.
[0029] Furthermore, if the proportion of molecules with a molecular weight of 100,000 or more in the molecular weight distribution of the binder resin is less than 10%, there is a risk of poor release properties at the high-temperature setting stage. On the other hand, if the proportion of molecules with a molecular weight of 100,000 or more in the molecular weight distribution of the binder resin exceeds 30%, there is a risk of poor low-temperature setting properties. By keeping this proportion below 20%, low-temperature setting properties can be made even more reliably good. Therefore, the preferred range for the proportion of molecules with a molecular weight of 100,000 or more in the molecular weight distribution of the binder resin is 10-20%.
[0030] The amount of binder resin in the toner matrix particles is preferably 60-90% by mass, and 70- A concentration of 85% by mass is particularly preferred.
[0031] (1-2-2) Colorants The colorants included in the toner of the present invention can be various types and colors of organic and inorganic pigments and dyes commonly used in the art, such as black, white, yellow, orange, red, purple, blue, and green colorants.
[0032] Examples of black colorants include carbon black, copper oxide, manganese dioxide, aniline black, activated carbon, non-magnetic ferrite, magnetic ferrite, and magnetite. Examples of white colorants include zinc oxide, titanium dioxide, antimony white, and zinc sulfide.
[0033] Examples of yellow colorants include lead yellow, zinc yellow, cadmium yellow, iron yellow, mineral fast yellow, nickel titanium yellow, navel yellow, naphthol yellow S, Hansa yellow G, Hansa yellow 10G, benzidine yellow G, benzidine yellow GR, quinoline yellow lake, permanent yellow NCG, tartrazine lake, CI pigment yellow 12, CI pigment yellow 13, CI pigment yellow 14, CI pigment yellow 15, CI pigment yellow 17, CI pigment yellow 93, CI pigment yellow 94, and CI pigment yellow 138.
[0034] Examples of orange colorants include red lead, molybdenum orange, permanent orange GTR, pyrazolone orange, balkan orange, induthrene brilliant orange RK, benzidine orange G, induthrene brilliant orange GK, CI pigment orange 31, and CI pigment orange 43.
[0035] Examples of red colorants include red iron oxide, cadmium red, red lead, mercury sulfide, cadmium, permanent red 4R, lysol red, pyrazolone red, watching red, calcium salt, lake red C, lake red D, brilliant carmine 6B, eosin lake, rhodamine lake B, alizarin lake, brilliant carmine 3B, CI pigment red 2, CI pigment red 3, CI pigment red 5, CI pigment red 6, CI pigment Examples include CI Pigment Red 7, CI Pigment Red 15, CI Pigment Red 16, CI Pigment Red 48:1, CI Pigment Red 53:1, CI Pigment Red 57:1, CI Pigment Red 122, CI Pigment Red 123, CI Pigment Red 139, CI Pigment Red 144, CI Pigment Red 149, CI Pigment Red 166, CI Pigment Red 177, CI Pigment Red 178, and CI Pigment Red 222.
[0036] Examples of purple colorants include manganese purple, fast violet B, and methyl violet lake. Examples of blue colorants include Prussian blue, cobalt blue, alkali blue lake, Victoria blue lake, phthalocyanine blue, metal-free phthalocyanine blue, partially chlorinated phthalocyanine blue, First Sky Blue, Induthlene Blue BC, CI Pigment Blue 15, CI Pigment Blue 15:2, CI Pigment Blue 15:3, CI Pigment Blue 16, and CI Pigment Blue 60. Examples of green colorants include chromium green, chromium oxide, pigment green B, micalite green lake, final yellow green G, and CI pigment green 7.
[0037] In the toner of the present invention, one of the above-mentioned colorants can be used alone or in combination of two, and these combinations may be of different colors or the same color. Furthermore, two or more colorants may be used as composite particles. These composite particles can be produced, for example, by adding appropriate amounts of water, lower alcohol, etc., to two or more colorants, granulating them in a general granulator such as a high-speed mill, and then drying them. In addition, to uniformly disperse the colorants in the binder resin, they may be used as a masterbatch. The composite particles and masterbatch are mixed into the toner composition during dry mixing.
[0038] The colorant content in the toner of the present invention is not particularly limited, but is preferably 0.1 to 20 parts by mass, and more preferably 0.2 to 10 parts by mass, per 100 parts by mass of the binder resin. If the colorant content is within the above range, it is possible to form an image with high image density and very good image quality without impairing the various physical properties of the toner. In terms of conversion, the colorant content in the toner is preferably 2.5 to 7.5% by mass, and more preferably 3.0 to 6.5% by mass.
[0039] (1-2-3) Release agent As the release agent included in the toner of the present invention, release agents commonly used in the art can be used. Examples include petroleum-based waxes such as paraffin wax and microcrystalline wax and their derivatives; hydrocarbon-based synthetic waxes such as Fischer-Tropsch wax, polyolefin waxes (polyethylene wax, polypropylene wax, etc.), low molecular weight polypropylene wax and polyolefin polymer waxes (low molecular weight polyethylene wax, etc.) and their derivatives; plant-based waxes such as carnauba wax, rice wax and candelilla wax and their derivatives, and wood wax; animal-based waxes such as beeswax and whale wax; oil-based synthetic waxes such as fatty acid amides and phenolic fatty acid esters; long-chain carboxylic acids and their derivatives; long-chain alcohols and their derivatives; silicone polymers; and higher fatty acids. Among these, hydrocarbon-based waxes are preferred. The above derivatives include oxides, block copolymers of vinyl monomers and waxes, and graft-modified products of vinyl monomers and waxes. In the present invention, one of the above-mentioned release agents can be used alone or in combination of two or more.
[0040] The release agent preferably has a melting point of 70°C or lower, particularly from the viewpoint of achieving both low-temperature fixing and hot-off resistance of the toner in the belt fixing device. The lower limit of the melting point is about 60°C.
[0041] The content of the release agent in the toner of the present invention is not particularly limited, but is preferably 0.2 to 20 parts by mass, more preferably 0.5 to 10 parts by mass, and especially preferably 1.0 to 8.0 parts by mass, per 100 parts by mass of the binder resin. If the release agent content is within the above range, it is possible to form images with high image density and very good image quality without impairing the various physical properties of the toner. In terms of conversion, the release agent content in the toner is preferably 2.0 to 7.0% by mass, and more preferably 3.0 to 5.0% by mass.
[0042] (1-2-4) Antistatic agents The toner matrix particles of the present invention may contain a charge control agent, but it is preferable that they do not contain a charge control agent in order to suppress an increase in the amount of charge. As the charge control agent, charge control agents commonly used in the art for controlling negative charge can be used. Examples of charge control agents for controlling negative charge include oil-soluble dyes such as oil black and spiron black, metal-containing azo compounds, azo complex dyes, metal naphthenates, metal complexes and metal salts of salicylic acid and its derivatives (metals such as chromium, zinc, and zirconium), boron compounds, fatty acid soaps, long-chain alkyl carboxylates, and resin acid soaps. In the toner of the present invention, one of the above-mentioned charge control agents can be used alone or in combination of two or more.
[0043] The content of the charge control agent in the toner of the present invention is not particularly limited, but is preferably 0.5 to 3 parts by mass, and more preferably 1 to 2 parts by mass, per 100 parts by mass of the binder resin. If the content of the charge control agent is within the above range, it is possible to form an image with high image density and very good image quality without impairing the various physical properties of the toner. In terms of conversion, the content of the charge control agent in the toner is preferably 0.8% by mass or less.
[0044] (1-3) Average primary particle size of toner The toner of the present invention preferably has an average primary particle diameter of 4 to 10 μm. If the average primary particle diameter is less than 4 μm, the particle size of the toner matrix becomes too small, which may lead to high charge and poor fluidity. When this high charge and poor fluidity occur, it becomes impossible to stably supply toner to the photoreceptor, which may result in background blur and a decrease in image density. On the other hand, if the average primary particle diameter exceeds 10 μm, the particle size of the toner matrix becomes large, the layer thickness of the formed image increases, and the image becomes noticeably granular, making it undesirable as it is impossible to obtain a high-resolution image. In addition, the specific surface area decreases as the particle size of the toner matrix increases, and the amount of charge on the toner decreases. When the amount of charge on the toner decreases, the toner cannot be stably supplied to the photoreceptor, which may cause in-machine contamination due to toner scattering. A more preferable average primary particle diameter is 5 to 7 μm.
[0045] (2) Toner manufacturing method The toner matrix particles used in the present invention can be manufactured by known methods using known apparatus commonly used in the art, for example, by a mixing step of mixing a coarsely ground molten kneaded material containing at least a binder resin, a colorant, and a release agent with a filler; a fine grinding step of finely grinding the mixture obtained in the mixing step; a classification step of classifying the finely ground material obtained in the fine grinding step; and a spheroidizing step of spheroidizing the classified material obtained in the classification step using hot air. Compared to the wet method, the dry method is preferable because it involves fewer steps and lower equipment costs, and among these, the pulverization method is particularly preferable. The conditions in each process should be set appropriately depending on the material being worked with and the desired physical properties.
[0046] For mixing, known devices commonly used in the relevant art, such as Henschel-type mixing devices including the Henschel mixer (trade name, manufactured by Mitsui Mining Co., Ltd. (now Nippon Coke Industries Co., Ltd.)), Super Mixer (trade name, manufactured by Kawata Corporation), and MechanoMill (trade name, manufactured by Okada Seikou Co., Ltd.), as well as mixing devices such as the OngMill (trade name, manufactured by Hosokawa Micron Corporation), Hybridization System (trade name, manufactured by Nara Machine Works Co., Ltd.), and Cosmo System (trade name, manufactured by Kawasaki Heavy Industries, Ltd.), can be used. For melt mixing, commonly known equipment used in the relevant art, such as twin-screw extruders, three-roll kneaders, and lab blast mills, can be used. Specifically, for example, single-screw or twin-screw extruders such as TEM-100B (trade name, manufactured by Toshiba Machine Co., Ltd.), PCM-65 / 87, and PCM-30 (all trade names, manufactured by Ikegai Co., Ltd.), and open-roll kneaders such as Nidex (trade name, manufactured by Mitsui Mining Co., Ltd.) can be used. For fine grinding, known devices commonly used in the art, such as a jet grinder that uses a supersonic jet stream to grind, or an impact grinder that introduces solidified material into the space formed between a high-speed rotating rotor and stator to grind it, can be used. For classification, known devices commonly used in the art, such as rotary wind classifiers (or rotary wind classifiers) that can remove over-pulverized toner particles by centrifugal force and wind force, can be used.
[0047] The toner of the present invention can be manufactured by a known method using a known apparatus commonly used in the art, comprising a first external addition step of externally adding external silica to toner matrix particles, and a second external addition step of externally adding externally adding fine particles. The conditions in each process should be set appropriately depending on the material being worked with and the desired physical properties.
[0048] (3) Two-component developer The toner of the present invention may also be a two-component developer containing a carrier. The toner of the present invention can be used in either the form of a one-component developer or a two-component developer. When used as a two-component developer, a carrier is further added in addition to the external additive. As carriers, carriers commonly used in the relevant art can be used, for example, single or composite ferrites and carrier core particles made of iron, copper, zinc, nickel, cobalt, manganese, chromium, etc., and surface-coated with known coating materials. The average particle size of the carrier is preferably 10 to 100 μm, and more preferably 20 to 50 μm. The amount of carrier is not particularly limited, but is preferably 4 to 15 parts by mass, and more preferably 5 to 10 parts by mass, per 100 parts by mass of toner matrix particles.
[0049] (4) Electrophotographic device The electrophotographic apparatus of the present invention is not particularly limited as long as it has the above-mentioned constituent requirements, but examples of image forming apparatus include an electrophotographic photoreceptor, a charging means for charging the electrophotographic photoreceptor, an exposure means for exposing the charged electrophotographic photoreceptor to form an electrostatic latent image, a developing means for developing the electrostatic latent image formed by exposure to form a toner image, a transfer means for transferring the toner image formed by development onto a recording medium, a fixing means for fixing the transferred toner image onto the recording medium to form an image, a cleaning means for removing and recovering toner remaining on the electrophotographic photoreceptor, and a static discharge means for discharging surface charge remaining on the electrophotographic photoreceptor. An example of an image forming apparatus and its operation will be described below with reference to the drawings, but the present invention is not limited thereto.
[0050] (4-1) Image forming apparatus
[0051] Figure 1 is a schematic side view showing the configuration of the main parts of the image forming apparatus 100 of the present invention. The image forming apparatus (laser printer) 100 in Figure 1 comprises the photoreceptor 1 of the present invention (corresponding to F01 in Figure 2), exposure means (semiconductor laser) 31, charging means (charger) 32, developing means (developer) 33, transfer means (transfer charger) 34, transport belt (not shown), fixing means (fixer) 35, and cleaning means (cleaner) 36. Reference numeral 51 indicates a recording medium (recording paper or transfer paper).
[0052] The photoreceptor 1 is rotatably supported on the main body of the image forming apparatus 100 and is rotationally driven around a rotation axis 44 in the direction of arrow 41 by a driving means (not shown). The driving means is composed of, for example, an electric motor and a reduction gear, and the driving force is transmitted to a conductive support that constitutes the core of the photoreceptor 1, thereby rotating the photoreceptor 1 at a predetermined peripheral speed. The charging means (charger) 32, exposure means 31, developing means (developer) 33, transfer means (transfer charger) 34, and cleaning means (cleaner) 36 are provided in this order along the outer circumferential surface of the photoreceptor 1, from the upstream side to the downstream side in the rotational direction of the photoreceptor 1, as indicated by arrow 41.
[0053] The charger 32 is a charging means that uniformly charges the outer surface of the photoreceptor 1 (corresponding to the photoreceptor F01 in Figure 2) to a predetermined potential. Examples of charging means include non-contact charging methods such as corona charging using a charging charger, and contact charging methods such as charging rollers or charging brushes. The exposure means 31 is equipped with a semiconductor laser as a light source, and the laser beam light output from the light source is irradiated onto the surface of the photoreceptor 1 between the charger 32 and the developer 33, thereby exposing the outer surface of the charged photoreceptor 1 according to the image information. The light is repeatedly scanned in the direction in which the rotation axis 44 of the photoreceptor 1 extends, which is the main scanning direction, and these images are formed to sequentially create an electrostatic latent image on the surface of the photoreceptor 1. That is, the amount of charge on the photoreceptor 1, which is uniformly charged by the charger 32, differs depending on whether it is irradiated with the laser beam or not, and an electrostatic latent image is formed.
[0054] The developing unit 33 is a developing means that develops the electrostatic latent image formed on the surface of the photoreceptor 1 by exposure using a developer (toner). It is provided facing the photoreceptor 1 and includes a developing roller 33a that supplies toner to the outer surface of the photoreceptor 1, and a casing 33b that supports the developing roller 33a so as to be rotatable around a rotation axis parallel to the rotation axis 44 of the photoreceptor 1 and houses a developer containing toner in its internal space.
[0055] The transfer charger 34 is a transfer means that transfers the toner image, which is a visible image formed on the outer surface of the photoreceptor 1 by development, onto the transfer paper 51, which is a recording medium supplied between the photoreceptor 1 and the transfer charger 34 from the direction of arrow 42 by a transport means (not shown). The transfer charger 34 is a contact-type transfer means that, for example, includes a charging means and transfers the toner image onto the transfer paper 51 by applying a charge of the opposite polarity to the toner to the transfer paper 51.
[0056] The cleaner 36 is a cleaning means for removing and recovering toner remaining on the outer surface of the photoreceptor 1 after the transfer operation by the transfer charger 34. It comprises a cleaning blade 36a for peeling off the toner remaining on the outer surface of the photoreceptor 1, and a recovery casing 36b for containing the toner peeled off by the cleaning blade 36a. The cleaner 36 is also provided together with an anti-static lamp (not shown).
[0057] Furthermore, the image forming apparatus 100 is provided with a fuser 35, which is a fixing means for fixing the transferred image, located downstream of the transfer paper 51 that has passed between the photoreceptor 1 and the transfer charger 34. The fuser 35 comprises a heating roller 35a having a heating means (not shown) and a pressure roller 35b provided opposite the heating roller 35a and pressed by the heating roller 35a to form a contact portion. Reference numeral 37 denotes a separation means for separating the transfer paper and the photoreceptor, and reference numeral 38 denotes a housing that accommodates the aforementioned means of the image forming apparatus.
[0058] The image forming operation by this image forming apparatus 100 is performed as follows. First, when the photoreceptor 1 is rotated in the direction of arrow 41 by the driving means, the surface of the photoreceptor 1 is uniformly charged to a predetermined positive potential by the charger 32, which is located upstream of the image point of the light formed by the exposure means 31 in the direction of rotation of the photoreceptor 1.
[0059] Next, the exposure means 32 irradiates the surface of the photoreceptor 1 with light corresponding to the image information. Through this exposure, the surface charge of the photoreceptor 1 is removed from the irradiated area, creating a difference in surface potential between the irradiated area and the unirradiated area, and an electrostatic latent image is formed. Toner is supplied from a developer 33 located downstream of the image point of light formed by the exposure means 33 in the rotational direction of the photoreceptor 1 to the surface of the photoreceptor 1 on which an electrostatic latent image has been formed, developing the electrostatic latent image and forming a toner image.
[0060] In sync with the exposure of the photoreceptor 1, transfer paper 51 is supplied between the photoreceptor 1 and the transfer charger 34. The transfer charger 34 imparts a charge of the opposite polarity to the toner to the supplied transfer paper 51, and the toner image formed on the surface of the photoreceptor 1 is transferred onto the transfer paper 51. The transfer paper 51 on which the toner image has been transferred is transported to the fuser 35 by a transport means, and as it passes through the contact area between the heating roller 35a and the pressure roller 35b of the fuser 35, it is heated and pressurized, fixing the toner image onto the transfer paper 51 to form a robust image. The transfer paper 51 with the image formed in this way is discharged to the outside of the image forming apparatus 100 by a transport means.
[0061] Meanwhile, any toner remaining on the surface of the photoreceptor 1 after the transfer of the toner image by the transfer charger 34 is peeled off and collected by the cleaner 36. The charge on the surface of the photoreceptor 1 from which the toner has been removed is removed by light from the static elimination lamp, and the electrostatic latent image on the surface of the photoreceptor 1 disappears. Subsequently, the photoreceptor 1 is further rotated, and the series of operations starting again from charging is repeated, so that an image is continuously formed.
[0062] The image forming apparatus 100 described above is a monochrome image forming apparatus (printer), but it may also be a color image forming apparatus using an intermediate transfer method that can form color images. Specifically, it may be a so-called tandem-type full-color image forming apparatus in which a plurality of electrophotographic photoreceptors, each on which a toner image is formed, are arranged in a predetermined direction (for example, horizontal direction H or approximately horizontal direction H). Furthermore, the image forming apparatus 100 may be another color image forming apparatus, copier, multifunction printer, or facsimile machine.
[0063] (4-2) Electrophotographic photoreceptor The photoreceptor in the image forming apparatus of the present invention comprises a top surface layer containing silica filler. By incorporating (dispersing) silica filler in the outermost layer, the photoreceptor becomes more resistant to mechanical stress, thus extending its lifespan. An example of a photoreceptor in the image forming apparatus of the present invention will be described below with reference to the drawings, but the present invention is not limited thereto. Figure 2 is a schematic cross-sectional view showing the main components of the photoreceptor (stacked photoreceptor) F01. The multilayer photoreceptor F01 comprises a photoreceptor layer on a substrate F1, in which an undercoat layer F21, a charge generating layer F22 containing a charge generating material, and a charge transport layer F23 containing a charge transport material are stacked in this order, with silica filler contained in the charge transport layer F23, which is the outermost layer. In the figure, Fa indicates the surface of the photoreceptor.
[0064] (4-3) Silica filler Examples of silica fillers include silica particles commonly used in the art, such as fumed silica obtained by burning silicon tetrachloride, dry silica particles such as arc silica produced by micronizing silica in the gas phase using high energy such as plasma; wet silica particles such as precipitated silica synthesized under alkaline conditions using an aqueous sodium silicate solution as a raw material, and gel silica synthesized under acidic conditions; colloidal silica particles obtained by polymerizing acidic silicic acid in an alkaline state; and sol-gel silica particles obtained by hydrolysis of organosilane compounds. These may be surface-treated with a surface treatment agent to improve the electrical properties of the photoreceptor. The silica filler content in the outermost layer is approximately 7-25% by mass.
[0065] The average primary particle size of the silica filler is not particularly limited, but is preferably 30 nm. When the average primary particle size of silica filler exceeds 30 nm, the aggregated structure formed in the outermost layer becomes larger, which can easily lead to problems such as poor cleaning. On the other hand, if the average primary particle size of silica filler is too small, sufficient print resistance may not be obtained, and the lower limit for this is around 7 nm. The preferred average primary particle size of silica filler is 10–20 nm. [Examples]
[0066] The present invention will be specifically described below with reference to examples and comparative examples, but the present invention is not limited to the following examples unless it exceeds the gist of the invention. In the examples and comparative examples, each physical property was measured by the method described below. In the following, "parts" and "%" refer to "parts by mass" and "% by mass," respectively, unless otherwise specified.
[0067] [Adhesion strength of external additives] The adhesion strength of the external additive is measured using the following procedure. (1) Add 2.0 g of toner to 40 ml of a 0.2% by mass aqueous solution of Triton (polyoxyethylene octylphenyl ether) and stir for 1 minute. (2) The above aqueous solution is further irradiated with ultrasonic waves at an output of 40 μA for 2 minutes using a homogenizer (manufactured by Nippon Seiki Seisakusho Co., Ltd., model: US-300T). (3) The aqueous solution after ultrasonic irradiation is left to stand for 3 hours to separate the toner from the liberated external additive. (4) After removing the supernatant liquid, add approximately 50 ml of pure water to the precipitate and stir for 5 minutes. (5) Perform suction filtration using a membrane filter with a pore size of 1 μm (manufactured by Advantec). (6) Vacuum dry any toner remaining on the filter overnight. (7) Using an X-ray fluorescence analyzer (manufactured by Rigaku Corporation, model: ZSX Primus II), the intensity of elements (Si, Ti) in 1 g of toner additive before and after the series of ultrasonic treatments described in (1) to (6) above is analyzed, and the adhesion strength α of the additive is calculated using the following formula. Adhesion strength of external additive a (%) = [(Fluorescence X-ray intensity of Si element after sonication) / (Fluorescence X-ray intensity of Si element before sonication)] × 100 Adhesion strength of external additive b(%) = [(X-ray fluorescence intensity of Ti element after sonication) / (X-ray fluorescence intensity of Ti element before sonication)] × 100 Adhesion strength α=b / a
[0068] [Average primary particle size of each external additive (nm)] The average primary particle diameter of each external additive is determined by imaging the particles using a scanning electron microscope (SEM) (Hitachi High-Technologies Corporation, model: S-4800), and calculating the 50% particle diameter based on the number of particles measured by the equivalent circle diameter from the obtained images. This is then defined as the average primary particle diameter.
[0069] [Average primary particle size of toner matrix particles (μm)] 20 mg of the sample and 1 ml of alkyl ether sulfate sodium were added to 50 ml of electrolyte (Beckman Coulter, Inc., product name: ISOTON-II), and the mixture was dispersed for 3 minutes at a frequency of 20 kHz using an ultrasonic disperser (AS ONE Corporation, benchtop dual-frequency ultrasonic cleaner, model: VS-D100) to obtain a sample for measurement. The obtained sample was measured using a particle size distribution analyzer (Beckman Coulter, Inc., model: Multisizer3) under conditions of aperture diameter: 100 μm and number of particles measured: 50,000 counts, and the average primary particle diameter (μm) was determined from the volume particle size distribution of the sample particles.
[0070] [Coverage rate of external additives] Assuming that the entire surface of the toner matrix particles is covered with the external additive in a close-packed state (100%), and that each particle of the external additive has the same average primary particle diameter, the coating rate of the external additive is calculated from the average primary particle diameter of the external additive and the surface area of the toner matrix particles. Specifically, the coverage rate of the external additive is defined as the value obtained by dividing the total projected area of the external additive, calculated as follows, by the total surface area of the toner. First, the projected area per particle is calculated from the particle size of the external additive using the formula for the area of a circle. Next, the volume of the external additive is determined using the formula for the volume of a sphere, and the weight of the external additive is calculated by multiplying this by the specific gravity. Furthermore, the number of external additive particles per toner particle is calculated. The total amount of added weight and the weight of one particle of external additive are used to determine the total toner weight. The sum of the projected areas per particle is calculated from the number of external additive particles. The total surface area of the toner is determined from the surface area of one toner particle using the formula for the surface area of a sphere.
[0071] (Example 1) [Preparation of toner matrix particles] The toner matrix particles used in the examples and comparative examples were prepared as follows. Binding resin: Polyester resin (glass transition temperature 55°C, softening temperature 105°C) 100 parts by mass Coloring agent: Carbon black (manufactured by Mitsubishi Chemical Corporation, product name: MA-100) 10 parts by mass Release agent: Wax (microcrystalline wax, melting point 80℃, manufactured by Nippon Seiro Co., Ltd., product name: Hi-Mic-1070) 5 parts by mass
[0072] The above materials were mixed and dispersed for 3 minutes using an air-flow mixer (Henschel mixer, manufactured by Mitsui Mining Co., Ltd. (now Nippon Coke Industries Co., Ltd.), model: FM20C). Then, the mixture was melt-kneaded using a twin-screw extruder (manufactured by Ikegai Co., Ltd., model: PCM-30) under the conditions of cylinder temperature setting 110°C, barrel rotation speed 300 rpm, and raw material supply speed 20 kg / hour to obtain a kneaded product. The resulting mixture was cooled using a cooling belt, and then coarsely ground using a speed mill with a φ1 mm screen to obtain a coarsely ground product with a particle size of 1 mm. The obtained coarse material was finely ground using a counterjet mill (manufactured by Hosokawa Micron Corporation, model: AFG) to obtain a group of finely ground particles (finely ground material) with a volume average particle size of 6.2 μm. The obtained finely ground material was classified using a rotary classifier (manufactured by Hosokawa Micron Corporation, model: TSP separator) to obtain unadded toner base particles with a volume-average particle size of 6.7 μm.
[0073] [Preparation of externally added fine powders] After de-ironating and bleaching the metatitanic acid obtained by the sulfuric acid method, a sodium hydroxide aqueous solution was added to adjust the pH to 9.0 for desulfurization. Subsequently, the pH was neutralized to 5.8 with hydrochloric acid, and the mixture was filtered and washed to obtain a washed cake. Water was added to the washed cake to form a slurry, and hydrochloric acid was added to adjust the pH to 1.4 for dispactation. The obtained metatitanic acid was placed in a reaction vessel, and strontium chloride solution and sodium silicate were added. Next, the mixture was heated to 90°C while stirring, and a 10N sodium hydroxide aqueous solution was added over 2 hours. After that, stirring was continued at 95°C for 1 hour to complete the reaction. After the reaction was complete, the resulting slurry was cooled to 50°C, and hydrochloric acid was added until the pH reached 5.0, followed by stirring for 1 hour. The resulting precipitate was decanted and washed, and then solid-liquid separation was performed by filtration. Next, the obtained solid was subjected to hydrophobic treatment with a silane compound, followed by solid-liquid separation by filtration. The solid was then dried at 120°C in air for 10 hours to obtain an externally added fine powder mainly composed of strontium titanate (molar ratio of silicon Si of silica to titanium Ti of strontium titanate: Si / Ti = 0.058). The number-average primary particle size was 40 nm.
[0074] [External processing] The obtained toner matrix particles and silica particles (average primary particle size 7 nm, manufactured by Nippon Aerosil Co., Ltd., product name: R976) as an external silica additive in an amount equivalent to 100% coverage of the toner matrix particles were placed in an FM mixer (manufactured by Nippon Coke Co., Ltd., model: FM-20), and the peripheral speed at the outermost circumference of the tip of the stirring blade was set to 40 m / sec and mixed for 1 minute (first external additive step). Next, an amount of externally added fine powder equivalent to a 5% coating rate on the toner base particles was added to the FM mixer, the peripheral speed at the outermost tip of the stirring blade was set to 40 m / sec, and the mixture was mixed for 1.5 minutes (second external addition step). The resulting mixture was sieved using a 270-mesh sieve to obtain an external toner.
[0075] [Preparation of developer] The obtained external toner and coat carrier (manufactured by Sharp Corporation, name: genuine carrier for MX-5111FN) were placed in a V-type mixer (manufactured by Tokuju Kogyosho Co., Ltd., product name: V-5) to obtain a two-component developer by mixing for 20 minutes so that the toner concentration was 7% by mass.
[0076] (Example 2) In the [External Addition Process], the toner and two-component developer were obtained and evaluated in the same manner as in Example 1, except that silica particles (average primary particle size 16 nm, manufactured by Nippon Aerosil Co., Ltd., product name: R972) were used as the external silica additive.
[0077] (Example 3) In the [External Addition Process], the toner and two-component developer were obtained in the same manner as in Example 1, except that silica particles (average primary particle diameter 40 nm, manufactured by Nippon Aerosil Co., Ltd., product name: RY50) were used as the external silica additive, and these were then evaluated.
[0078] (Example 4) In the [external additive treatment], the toner and two-component developer were obtained and evaluated in the same manner as in Example 1, except that the amount of externally added silica was set to an amount equivalent to a 20% coverage rate on the toner matrix particles.
[0079] (Example 5) In the [external additive treatment], the toner and two-component developer were obtained and evaluated in the same manner as in Example 1, except that the amount of externally added silica was set to an amount equivalent to a 150% coverage rate on the toner matrix particles.
[0080] (Example 6) In the [external additive treatment], the toner and two-component developer were obtained and evaluated in the same manner as in Example 1, except that the amount of externally added fine powder was set to an amount equivalent to a 1% coverage rate on the toner base particles.
[0081] (Example 7) In the [external additive treatment], the toner and two-component developer were obtained and evaluated in the same manner as in Example 1, except that the amount of externally added fine powder was set to an amount equivalent to a 20% coverage rate on the toner base particles.
[0082] (Example 8) In the [External Addition Process], the toner base particles for which external addition conditions for externally added fine particles were obtained, along with silica particles as externally added silica equivalent to 100% coverage of the toner base particles, were placed in an FM mixer. The peripheral speed at the outermost circumference of the stirring blade tip was set to 40 m / sec, and the mixture was stirred for 1.5 minutes (first external addition step). Next, an amount of externally added fine powder equivalent to 5% coverage of the toner base particles was placed in the FM mixer, and the peripheral speed at the outermost circumference of the stirring blade tip was set to 30 m / sec, and the mixture was stirred for 0.5 minutes (second external addition step). Except for setting the ratio b / a of the adhesion strength b of the externally added fine powder to the adhesion strength a of the externally added silica to 0.1, the toner and two-component developer were obtained in the same manner as in Example 1 and evaluated.
[0083] (Example 9) In the [External Addition Process], the toner base particles for which external addition conditions for externally added fine particles were obtained, along with silica particles as externally added silica in an amount equivalent to 100% coverage of the toner base particles, were placed in an FM mixer, the peripheral speed at the outermost circumference of the tip of the stirring blade was set to 30 m / sec, and the mixture was mixed for 0.5 minutes (first external addition step). Then, an amount equivalent to 5% coverage of the toner base particles was placed in the FM mixer, the peripheral speed at the outermost circumference of the tip of the stirring blade was set to 40 m / sec, and the mixture was mixed for 1.5 minutes (second external addition step). Except for setting the ratio b / a of the adhesion strength b of the externally added fine powder to the adhesion strength a of the externally added silica to 0.6, the toner and two-component developer were obtained in the same manner as in Example 1 and evaluated.
[0084] (Comparative Example 1) In the preparation of toner matrix particles, toner and a two-component developer were obtained in the same manner as in Example 1, except that 2 parts by mass of a charge control agent (manufactured by Hodogaya Chemical Co., Ltd., product name: TRH) were used, and these were evaluated.
[0085] (Comparative Example 2) The toner and two-component developer obtained in the same manner as in Example 1 were evaluated using an image forming apparatus equipped with an electrophotographic photoreceptor having a surface layer that does not contain silica filler.
[0086] (Comparative Example 3) In the [external additive treatment], toner and two-component developer were obtained and evaluated in the same manner as in Example 1, except that externally added fine powder was not added.
[0087] <Rating> <Evaluation 1: Low-temperature fixation> A commercially available copier (manufactured by Sharp Corporation, model: MX-5100FN) modified for evaluation purposes was used to form fixed images using a two-component developer. First, a sample image containing a solid color image (a rectangle measuring 20 mm vertically and 50 mm horizontally) was formed as an unfixed image on recording paper (Sharp Corporation, PPC paper, model: SF-4AM3). At this time, the amount of toner adhering to the recording paper in the solid color image was 0.5 mg / cm². 2 I adjusted it so that it would work. Next, a fixed image was created using a hard roller fixing device. The fixing process speed was set to 120 mm / second, and the temperature of the fixing roller was increased in 5°C increments starting from 140°C to determine the lowest temperature at which low-temperature offset occurred.
[0088] "Low-temperature offset" is defined as the phenomenon where toner does not adhere to the recording paper during the fixing process, but instead remains attached to the fixing belt until it completes one rotation before adhering to the recording paper. Based on the results obtained, "low-temperature fixation ability" was determined according to the following criteria. ○: Good (Offset occurs at a temperature of 160℃) △: Possible (Offset occurs at a temperature of 165℃) ×: Not possible (The temperature at which the offset occurs is 170℃)
[0089] <Evaluation 2: Stability of the electrostatic environment (environmental fluctuations)> A two-component developer was obtained by mixing toner with a ferrite core carrier having an average primary particle size of 60 μm, so that the toner concentration was 5% by mass. Using a suction-type electrostatic measuring device (Trek Japan, Model: 210HS), the charge amount Q1 of the obtained two-component developer at normal temperature and humidity (20°C, 50%RH) and the charge amount Q2 at high temperature and high humidity (35°C, 85%) were measured. As an indicator of the stability of the electrostatic environment, the ratio of charge amount Q1 to charge amount Q2, Q2 / Q1 × 100 [%], was calculated.
[0090] Based on the results obtained, the "static environment stability" was determined according to the following criteria. ○: Good (Ratio Q2 / Q1 × 100 is 60% or higher) △: Acceptable (Ratio Q2 / Q1 × 100 is 50% or more but less than 60%) ×: Not acceptable (Ratio Q2 / Q1 × 100 is less than 50%)
[0091] <Rating 3: Polishing (scratches) on the photoreceptor> The surface of the photoreceptor was visually inspected after evaluation of its low-temperature fixability and judged according to the following criteria. ○: Good (No noticeable scratches) △: Acceptable (Has some damage, but the impact is minor and it is still usable) ×: Unacceptable (The damage is significant and makes it unusable for practical purposes)
[0092] <Rating 4: Filming> In evaluating low-temperature fixation, all solid prints were visually observed and judged according to the following criteria. ○: Good (No problems with printing) △: Acceptable (There is some filming in the printed area, but the impact is minor and it is still usable.) ×: Not acceptable (There is a problem with the printing area, which has a significant impact and makes it unsuitable for practical use)
[0093] <Overall Rating> The results of evaluations 1-4 were comprehensively evaluated (judged) according to the following criteria. ○: Good (○ only) △: Practical level (no ×s, and at least one △) ×: Defective (at least one × is present) Table 1 summarizes the evaluation results along with the conditions for the photoreceptor, toner, and external additives.
[0094] [Table 1]
[0095] From the results in Table 1, the following can be seen: (1) The toner and developer of the present invention (Examples 1-9) can achieve low-temperature fixing and long life. (2) When the average primary particle size of the added silica is large, the low-temperature fixation and stability in the electrostatic environment decrease (Example 3). (3) When the amount of externally added silica is small (low coverage), the stability of the electrostatic environment decreases (Example 4), while when the amount of externally added silica is large (high coverage), the low-temperature fixation performance decreases (Example 5). (4) When the amount of externally added fine powder is small (low coverage), the stability in the electrostatic environment decreases (Example 6), while when the amount of externally added silica is large (high coverage), the low-temperature fixation performance decreases (Example 7). (5) When the ratio b / a of the adhesion strength b of the externally added fine powder to the adhesion strength a of the externally added silica is small, the stability of the electrostatic environment decreases (Example 8), while when the ratio b / a is large, filming is more likely to occur (Example 9).
[0096] (6) When the toner matrix particles contain a charge control agent, the low-temperature fixing properties are poor, and the desired low-temperature fixing properties cannot be ensured (Comparative Example 1). (7) When not used in an image forming apparatus equipped with an electrophotographic photoreceptor having a surface layer containing silica filler, scratches occur on the photoreceptor (polishing of the photoreceptor), filming occurs, and the device becomes unsuitable for practical use (Comparative Example 2). (8) If the externally added fine powder is not added, the stability of the electrostatic environment decreases, filming occurs, and the product is not suitable for practical use (Comparative Example 3).
[0097] According to the present invention, the following effects are expected to be obtained. • The addition of silica provides the effect of imparting electrostatic properties and fluidity. - By adding strontium titanate fine powder, which is conductive and has the function of transferring the negative charge of locally charged toner particles to surrounding toner particles or releasing it into the air when added to the toner surface, to the toner together with small-particle silica, the amount of charge can be adjusted to an appropriate level without impairing the effect of silica in providing fluidity to the toner. • By adding strontium titanate fine powder to the toner surface with weak adhesion strength, the additive that detaches from the toner surface is present between the photoreceptor drum and the cleaning roller, improving the cleaning performance of the drum surface. • If the toner does not contain a charge control agent, the fixing area extends to the lower temperature side, enabling even lower temperature fixing. • By using an electrophotographic photoreceptor (silica filler drum) with a top surface layer containing silica filler, drum wear is reduced, resulting in a longer lifespan. [Explanation of Symbols]
[0098] F01 Stacked Electrophotographic Photoconductor F1 Substrate (conductive support) F21 Lower layer (intermediate layer) F22 Charge Generation Layer F23 Charge transport layer Fa Photoreceptor surface
[0099] 31. Exposure means (semiconductor laser) 32. Charging means (charger) 33. Developing means (developer) 33a Developing roller 33b Casing 34 Transfer means (transfer charger) 35 Fixing means (fuser) 35a Heating roller 35b Pressure roller 36. Cleaning methods (cleaners) 36a Cleaning Blade 36b Recovery casing 37 Separation means 38 Housing 41, 42 arrow mark 44 Rotation axis 51 Recording medium (recording paper or transfer paper) 100 Image forming apparatus (laser printer)
Claims
1. An electrophotographic apparatus in which an electrostatic latent image is formed on the surface of an electrophotographic photosensitive member, and a toner developed on the electrostatic latent image is transferred to a transfer material to form an image, the electrophotographic photoreceptor has an outermost layer containing a silica filler, the toner comprises toner base particles containing at least a binder resin, a colorant, and a release agent, and an external additive; The electrophotographic apparatus is characterized in that the external additive is an externally added fine powder of silica and strontium titanate to which silica has been added, the core surface of which has been hydrophobized with a silane compound.
2. 2. The electrophotographic apparatus according to claim 1, wherein the amount of the externally added fine powder is an amount corresponding to a coverage of 2 to 10% of the toner base particles.
3. 3. The electrophotographic apparatus according to claim 1, wherein the ratio b / a of the adhesive strength b of the externally added fine powder to the toner base particles and the adhesive strength a of the externally added silica satisfies the relationship 0.15≦α≦0.
5.
4. 4. The electrophotographic apparatus according to claim 1, wherein the molar ratio Si / Ti of silicon (Si) of silica to titanium (Ti) of strontium titanate in the externally added fine powder is 0.03 or more and less than 1.
0.
5. 5. The electrophotographic apparatus according to claim 1, wherein the externally added silica has an average primary particle size of 6 to 17 nm.
6. 6. The electrophotographic apparatus according to claim 1, wherein the amount of the externally added silica is an amount corresponding to a coverage rate of 50 to 120% of the toner base particles.
7. 7. The electrophotographic apparatus according to claim 1, wherein the toner base particles do not contain a charge control agent.
8. 8. The electrophotographic apparatus according to claim 1, wherein the toner is a two-component developer containing a carrier.